Effects of Peers and Family Members on Smoking Habits in Adolescents: A Meta-Analysis - Florida Betty Apriliyani; Agus Kristiyanto; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: Nowadays, smoking is one of the biggest public health problems worldwide. It is a major cause of disease and mortality that can be prevented early. One out of 10 deaths worldwide is caused by tobacco use. 40 million people died each year due to tobacco. Adolescents start smoking in response to social effects, imitating the behavior of friends, family members, and others they admire. This meta-analysis study aimed to analyze the effect of peers and family members who smoked on smoking habits in adolescents.Subjects and Method: Meta-analysis was conducted by searching for articles from databases such as PubMed, SpringerLink, Elsevier, Science Direct, and Google Scholar. The keywords were "peers" OR "parenting style" OR "family influence" AND "smoking" AND "behavior" AND "adolescents" AND "cross-sectional". The inclusion criteria were full-text articles with a cross-sectional design, English and Indonesian languages, students aged 14-24 years as the study subjects. The final results of the study were presented using the adjusted odds ratio (aOR). The articles were analyzed using Revman 5.3 software.Results: 17 articles were analyzed. The results showed that peers and family members increased smoking habits in adolescents; the result was statistically significant with peers (aOR= 2.77; 95% CI= 1.67 to 4.60; p <0.001; I2= 96%) and family members (aOR= 1.69; 95% CI= 1.35 to 2.13; p<0.001; I2=65%).Conclusion: Peers and family members affects smoking habits in adolescents. It is statistically significant.Keywords: Peers, family members, smoking habits, adolescents, cross-sectionalCorrespondence: Florida Betty Apriliyani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ridhaflorida@gmail.com. Mobile: 081329329417.Journal of Health Promotion and Behavior (2020), 05(04): 248-263https://doi.org/10.26911/thejhpb.2020.05.04.03.